Fakes news” viruses in the COVID-19 pandemic - Naldo Balarezo-López, Gunther (2021)
COVID-19 is not only a contagious virus, it is also surrounded bay fake news which could lead individuals to experience anxiety, anguish, and even stress. Therefore, literature has been revised including of the most relevant points with the objective of describing aspects relating to the infodemic and false conspiracy theories that have been circulating through the media and social networks. during the year 2020. It was found that the fake news was propagating quicker than the virus itself, primarily due to personal, collective, economic and political interests. Nonetheless, it is recommended that the best way to fight fake news is not to spread messages before having verified the information in official and authorized sources.